Managing Disputes at the Level of Administrative Departments - Guaoui, Said (Journal of Legal Studies and Researches, 2024)
Each administrative body has one of its functions to follow up on disputes that arise within the authority or with others. The present paper highlights the role of the Dispute Office in contributing to the defence of the governing body's interests through the processing of files and documents and the preparation of petitions and reply notes.